High-temperature-resistant solid-liquid hybrid capacitor and preparation method thereof

By optimizing the composition of the conductive polymer dispersion and electrolyte, and introducing additives such as nano-copper oxide and sodium salt, a dense and stable solid electrolyte layer was constructed, which solved the problem of poor stability of solid-liquid hybrid capacitors at high temperatures and achieved long-term stable operation at 150℃.

CN121483882APending Publication Date: 2026-02-06JIANG HUA BERYL NEW ENERGY STORAGE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511809687.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-11-07
Filing Date
2025-12-03
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing solid-liquid hybrid capacitors exhibit poor stability at temperatures of 150°C and above, failing to meet the high-temperature reliability requirements of fields such as aerospace and new energy vehicles.

Method used

By optimizing the composition of conductive polymer dispersion and electrolyte, introducing nano-copper oxide and sodium salt, and using a composite electrolyte additive system containing chloride, sulfate, inorganic polymer iron salt and heavy metal compounds, a dense and stable solid electrolyte layer is constructed to repair defects in the anodic oxide film and improve the interfacial contact state.

Benefits of technology

It significantly improves the long-term stability of capacitors at 150℃, controls the capacitance decay rate to within -1.5%, and reduces the variation of equivalent series resistance and loss factor, thus meeting the requirements of high-temperature operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005720385200000061
    Figure BDA0005720385200000061
  • Figure BDA0005720385200000071
    Figure BDA0005720385200000071
  • Figure BDA0005720385200000081
    Figure BDA0005720385200000081
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant solid-liquid hybrid capacitor and a preparation method thereof. The preparation method of the capacitor comprises the steps of element winding, formation repairing, drying, conductive polymer dispersion liquid impregnation, thermal polymerization, electrolyte impregnation, packaging and aging. The core of the conductive polymer dispersion liquid is that the conductive polymer dispersion liquid comprises a polymer monomer, doped acid, nano copper oxide and sodium salt; the electrolyte comprises chloride, sulfate, inorganic polymer ferric salt and a heavy metal compound as additives. Through the synergistic enhancement of the nano copper oxide and the sodium salt in the solid electrolyte layer and the repair protection of the electrolyte additive, the performance stability of the solid-liquid hybrid capacitor in a high-temperature environment of 150 DEG C or above is effectively improved. After the capacitor prepared by the method is aged for 2000 hours in a high-temperature environment of 150 DEG C, the capacitance attenuation rate can be controlled within-1.5%, and the capacitor shows excellent high-temperature stability and reliability and is suitable for the fields of aerospace, automotive electronics and the like which have harsh requirements on high-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of capacitors, and more particularly to a high-temperature-resistant solid-liquid hybrid capacitor and a preparation method thereof. BACKGROUND

[0002] Capacitors are one of the three basic passive electronic components, and play a key role in electronic circuits such as tuning, filtering, coupling, bypassing and energy conversion. Among them, aluminum electrolytic capacitors have more than 30% market share due to their high unit volume capacity and cost-effective advantages, and are widely used in consumer electronics, communications, industrial control and emerging new energy vehicles and variable frequency technology fields.

[0003] With the development of electronic devices towards high frequency, miniaturization and high reliability, the market has put forward more stringent requirements for the performance of aluminum electrolytic capacitors. Under this background, solid and solid-liquid hybrid capacitors have emerged. Compared with traditional liquid aluminum electrolytic capacitors, they have higher reliability, longer service life, lower equivalent series resistance and no risk of liquid leakage, and have become an important direction for industrial upgrading.

[0004] Chinese patent application CN112435863A discloses an optimized solid-liquid hybrid capacitor manufacturing method, which effectively solves the problems of complex process, additive waste, poor product consistency and easy moisture absorption of traditional impregnation methods by "after the core contains the impregnated polymer, the additive is quantitatively injected into the shell, and then sealed after vacuumizing". The production efficiency and product reliability are significantly improved. However, the existing technology mainly focuses on the optimization of production process, and does not provide an effective material solution for the long-term stability of capacitors in extreme working environments, especially the durability at temperatures of 150°C and above.

[0005] At present, the upper limit of the long-term working temperature of conventional solid-liquid hybrid capacitors is generally 135°C. At severe high temperatures of 150°C and above, the internal conductive polymer solid electrolyte layer and electrolyte system face serious challenges and are prone to degradation, volatilization and oxidative decomposition, leading to rapid deterioration of capacitor electrical performance, which cannot meet the urgent demand for high-temperature reliability in the fields of aerospace, automotive electronics, etc.

[0006] Therefore, there is an urgent need in the art for a new solid-liquid hybrid capacitor and a preparation method thereof that can significantly improve the high-temperature resistance of the product while ensuring product process yield and basic electrical characteristics, so that it can work stably in a 150°C environment for a long time. SUMMARY

[0007] Therefore, it is necessary to solve the above technical problems, and the present application provides a high-temperature-resistant solid-liquid hybrid capacitor and a preparation method thereof.

[0008] In order to solve the above technical problems, the present application provides a preparation method of a high-temperature-resistant solid-liquid mixed capacitor, which comprises the following steps:

[0009] S1, element winding: intervening electrolytic paper between the anode foil and the cathode foil, and winding into a core package;

[0010] S2, formation repair: immersing the core package into a formation liquid to perform repair treatment of the anode oxide film;

[0011] S3, drying treatment: baking the core package after the formation repair to remove moisture;

[0012] S4, conductive polymer dispersion liquid immersion: immersing the dried core package into a conductive polymer dispersion liquid;

[0013] S5, thermal polymerization: baking the immersed core package to make monomers polymerize to form a conductive polymer solid electrolyte layer;

[0014] S6, electrolyte immersion: immersing the polymerized core package into an electrolyte;

[0015] S7, packaging: packaging the core package after the electrolyte immersion into a shell and sealing;

[0016] S8, aging: performing aging treatment on the packaged capacitor;

[0017] The conductive polymer dispersion liquid comprises polymer monomers, doping acid, nano copper oxide and sodium salt.

[0018] Further, the composition of the conductive polymer dispersion liquid comprises 14% to 19% of polymer monomers, 0.25% to 0.35% of doping acid, 0.55% to 0.65% of nano copper oxide, 0.1% to 0.2% of sodium salt, and the balance of pure water.

[0019] Further, the electrolyte comprises a solvent and an additive, and the additive comprises chloride, sulfate, inorganic polymer iron salt and heavy metal compound.

[0020] Further, the polymer monomers are at least one of aniline, pyrrole, thiophene and derivatives thereof; the doping acid is at least one of organic sulfonic acid or organic carboxylic acid; and the sodium salt is at least one of sodium chloride, sodium sulfate, sodium nitrate, sodium acetate and sodium citrate.

[0021] Further, the particle size of the nano copper oxide is 25nm to 45nm.

[0022] Further, the composition of the electrolyte includes, based on the total mass of the electrolyte: sulfolane 42% to 67%, gamma-butyrolactone 24.6% to 48%, ethylene glycol 5% to 10%, triethylamine phthalate 2.8% to 9%, and an additive 0.3% to 1%.

[0023] Further, the additive includes, based on the total mass of the electrolyte: chloride 0.15% to 0.5%, sulfate 0.05% to 0.3%, inorganic high-molecular iron salt 0.06% to 0.12%, and heavy metal compound 0.04% to 0.08%.

[0024] Further, the chloride is selected from at least one of ammonium chloride, sodium chloride, potassium chloride, and choline chloride; the sulfate is selected from at least one of ammonium sulfate, sodium sulfate, and magnesium sulfate; the inorganic high-molecular iron salt is selected from at least one of polymeric ferric sulfate and polymeric ferric chloride; and the heavy metal compound is selected from at least one of a lead-containing compound, a mercury-containing compound, a cadmium-containing compound, or a chromium-containing compound.

[0025] Further, in step S1, the electrolytic paper is a low-density mixed-fiber electrolytic paper; in step S5, the temperature of the baking is 140°C to 160°C, and the time is 25 to 35 minutes; steps S4 and S5 are repeated 3 to 5 times; step S4 is performed in a cyclic environment of vacuum and pressure alternation; and step S6 is performed in a vacuum environment.

[0026] The second aspect of the application provides a high-temperature-resistant solid-liquid hybrid capacitor prepared by the preparation method described above.

[0027] Compared with the prior art, the application has the following beneficial effects:

[0028] The application significantly improves the high-temperature stability of the solid-liquid hybrid capacitor by optimizing the composition of the conductive polymer dispersion liquid and the electrolyte. By introducing nano copper oxide and a specific sodium salt into the conductive polymer dispersion liquid, and using a composite electrolyte additive system containing chloride, sulfate, inorganic high-molecular iron salt, and heavy metal compound, a synergistic effect between materials is achieved. This synergistic effect improves product performance in two key ways: nano copper oxide as a catalytic center improves the efficiency of the polymerization reaction, and the sodium salt stabilizes the electronic structure of the polymer chain, both of which cooperatively build a dense and stable solid electrolyte layer; at the same time, the multi-component additive system in the electrolyte repairs defects in the anode oxide film, improves the interface contact state, and effectively inhibits electrochemical degradation at high temperatures.

[0029] The capacitor prepared by the method of the application is subjected to an accelerated aging test at 150 DEG C for 2000 hours, the average capacitance attenuation rate is strictly controlled within-1.5%, the change range of equivalent series resistance and loss factor is also significantly reduced, and the long-term use requirement under high-temperature working condition is fully met, thereby providing reliable technical support for popularization of solid-liquid hybrid capacitors in high-temperature application scenarios such as aerospace and new energy vehicles. DETAILED DESCRIPTION

[0030] In order for those skilled in the art to better understand the application scheme, the technical solutions in the embodiments of the application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the application, not all. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor should belong to the protection scope of the application.

[0031] In order for those skilled in the art to better understand the application scheme, the technical solutions in the embodiments of the application will be clearly and completely described below.

[0032] Embodiment 1

[0033] The embodiment provides a preparation method of a high-temperature-resistant solid-liquid hybrid capacitor, which comprises the following steps:

[0034] S1, element winding: intervening electrolytic paper between the anode foil and the cathode foil, and winding into a core package;

[0035] The anode foil is a high-voltage-resistant low-specific-capacity anode foil, and the electrolytic paper is a low-density mixed-fiber electrolytic paper, which has the characteristics of fast liquid absorption speed, high tensile strength and high-temperature resistance.

[0036] S2, formation repair: immersing the wound core package in step S1 into a formation liquid to repair the anode oxide film.

[0037] S3, drying treatment: placing the core package after formation repair in a baking equipment to perform high-temperature baking to completely remove the moisture inside the core package.

[0038] S4, conductive polymer dispersion liquid immersion:

[0039] In a vacuum and pressure alternating cycle environment, the core package after drying treatment is immersed in the prepared conductive polymer dispersion liquid, so that the dispersion liquid is fully infiltrated and adsorbed on the electrolytic paper and the electrode foil.

[0040] The conductive polymer dispersion liquid is composed of the following components in mass percentage: pure water 82%, polymer monomer 17%, doped acid 0.3%, nano copper oxide 0.6%, and sodium salt 0.1%;

[0041] The particle size of the nano copper oxide is 25-45 nm.

[0042] The polymer monomer is at least one of aniline, pyrrole, thiophene and derivatives thereof; the doping acid is at least one selected from organic sulfonic acid, organic carboxylic acid, including but not limited to toluene sulfonic acid, benzene sulfonic acid, methyl sulfonic acid, dodecyl benzene sulfonic acid, camphor sulfonic acid, oxalic acid, citric acid, salicylic acid, acetic acid; the sodium salt is a compound capable of providing sodium ions, and is at least one selected from sodium chloride, sodium sulfate, sodium nitrate, sodium acetate, sodium citrate; specifically, in the embodiment, the polymer monomer is aniline, the doping acid is toluene sulfonic acid, and the sodium salt is sodium chloride.

[0043] S5, thermal polymerization: the core package after impregnation dispersion is placed in a polymerization oven, baked at 150°C for 30 minutes, so that the monomer is polymerized to form a conductive polymer solid electrolyte layer.

[0044] Steps S4 and S5 need to be repeated 3 times to build a dense and complete solid electrolyte layer.

[0045] S6, electrolyte impregnation: the core package after polymerization treatment is immersed in the prepared electrolyte in a vacuum environment, so that the electrolyte fully infiltrates the core package.

[0046] The electrolyte is composed of the following components with mass percentage: 52% of sulfolane, 34% of gamma-butyrolactone, 8% of ethylene glycol, 5.2% of triethylamine phthalate, and 0.8% of additives;

[0047] The additive contains the following components with mass fraction, based on the total mass of the electrolyte: 0.4% of chloride, 0.24% of sulfate, 0.1% of inorganic polymer iron salt, and 0.06% of heavy metal compound.

[0048] The chloride is at least one selected from ammonium chloride, sodium chloride, potassium chloride, and choline chloride; the sulfate is at least one selected from ammonium sulfate, sodium sulfate, and magnesium sulfate; the inorganic polymer iron salt is at least one selected from polymeric ferric sulfate and polymeric ferric chloride; the heavy metal compound is at least one selected from lead-containing compounds, mercury-containing compounds, cadmium-containing compounds, and chromium-containing compounds, including but not limited to: lead tetraphenylborate, basic lead sebacate, mercury nitrate, cadmium sulfate, and ammonium dichromate.

[0049] Specifically, in the embodiment, the chloride is ammonium chloride, the sulfate is ammonium sulfate, the inorganic polymer iron salt is polymeric ferric sulfate, and the heavy metal compound is lead tetraphenylborate.

[0050] S7, packaging: the core package after impregnation of the electrolyte is packaged in an aluminum shell, and a rubber plug is used to seal the opening of the aluminum shell to form a complete capacitor monomer.

[0051] S8, aging: the packaged capacitor is subjected to a stepwise voltage rise for aging treatment, and the final voltage is raised to 1.15 times the rated voltage to stabilize its electrical properties.

[0052] The 10 capacitor samples prepared in this embodiment were subjected to a 2000-hour durability test at 150°C high temperature environment, and the electrical property parameters before and after the test were tested. Embodiments 2-4 and Comparative Examples 1-5 all use the same method, and the performance test results of the capacitor prepared in Example 1 are shown in Table 1.

[0053] Table 1, high temperature durability test electrical property test results of capacitor samples of Example 1

[0054]

[0055] Example 2

[0056] The preparation method of this embodiment is different from that of Example 1 in that the formulation of the conductive polymer dispersion liquid and the electrolyte and the corresponding process parameters are adjusted, as follows:

[0057] S4, conductive polymer dispersion liquid immersion: in a vacuum and pressure alternating cycle environment, the core package subjected to drying treatment is immersed in the prepared conductive polymer dispersion liquid.

[0058] The conductive polymer dispersion liquid is composed of the following components in mass percentage: pure water 85%, polymer monomer 14%, doping acid 0.25%, nano copper oxide 0.65%, sodium salt 0.1%.

[0059] Specifically, in this embodiment, the polymer monomer is thiophene, the doping acid is camphor sulfonic acid, and the sodium salt is sodium citrate.

[0060] S5, thermal polymerization: the core package after immersion of the dispersion liquid is placed in a polymerization oven, baked at 140°C for 35 minutes, so that the monomer is polymerized to form a conductive polymer solid electrolyte layer.

[0061] Steps S4 and S5 need to be repeated 4 times to build a more dense and complete solid electrolyte layer.

[0062] S6, electrolyte immersion: in a vacuum environment, the core package subjected to polymerization treatment is immersed in the prepared electrolyte.

[0063] The electrolyte is composed of the following components in mass percentage: sulfolane 67%, γ-butyrolactone 24.6%, ethylene glycol 5%, triethylamine phthalate 2.8%, and additives 0.6%.

[0064] The additive comprises the following components in mass fraction, based on the total mass of the electrolyte: 0.15% of chloride, 0.3% of sulfate, 0.07% of inorganic high-molecular iron salt, and 0.08% of heavy metal compound.

[0065] Specifically, in the embodiment, the chloride is choline chloride, the sulfate is magnesium sulfate, the inorganic high-molecular iron salt is polyaluminum chloride, and the heavy metal compound is ammonium dichromate.

[0066] The remaining steps of the embodiment, such as S1 element winding, S2 formation repair, S3 drying treatment, S7 packaging, and S8 aging, are the same as those of Embodiment 1.

[0067] Table 2: Test results of high-temperature durability test and electrical performance of the capacitor samples of Embodiment 2

[0068]

[0069]

[0070] Embodiment 3

[0071] The embodiment provides a preparation method, which is different from that of Embodiment 1 in that the formulation of the conductive high-molecular dispersion liquid and the electrolyte and the corresponding process parameters are adjusted, and the specific adjustment is as follows:

[0072] S4, conductive high-molecular dispersion liquid immersion: under the alternating cycle of vacuum and pressure, the core package after drying treatment is immersed in the prepared conductive high-molecular dispersion liquid.

[0073] The conductive high-molecular dispersion liquid is composed of the following components in mass percentage: 80% of pure water, 19% of polymer monomer, 0.25% of doping acid, 0.55% of nano copper oxide, and 0.2% of sodium salt.

[0074] Specifically, in the embodiment, the polymer monomer is pyrrole, the doping acid is camphor sulfonic acid, and the sodium salt is sodium sulfate.

[0075] S5, thermal polymerization: the core package after the immersion dispersion liquid is placed in a polymerization oven, baked at 160°C for 25 minutes, so that the monomer is polymerized to form a conductive high-molecular solid electrolyte layer.

[0076] Steps S4 and S5 need to be repeated for 5 times to construct a more dense and complete solid electrolyte layer.

[0077] S6, electrolyte immersion: under vacuum environment, the core package after polymerization treatment is immersed in the prepared electrolyte.

[0078] The electrolyte is composed of the following components in mass percentage: 42% of sulfolane, 48% of gamma-butyrolactone, 5% of ethylene glycol, 4% of triethylamine phthalate, and 1% of additives.

[0079] The additives comprise the following components in mass percentage, based on the total mass of the electrolyte: 0.5% of chloride, 0.3% of sulfate, 0.12% of inorganic high-molecular iron salt, and 0.08% of heavy metal compound.

[0080] Specifically, in this embodiment, the chloride is potassium chloride, the sulfate is sodium sulfate, the inorganic high-molecular iron salt is polymeric ferric sulfate, and the heavy metal compound is basic lead sebacate.

[0081] The remaining steps of this embodiment, such as S1 element winding, S2 formation repair, S3 drying treatment, S7 packaging, and S8 aging, are the same as those of Embodiment 1.

[0082] Table 3: Test results of high-temperature durability test of the capacitor sample of Embodiment 3

[0083]

[0084] Embodiment 4

[0085] This embodiment provides a preparation method, which is different from that of Embodiment 1 in that the formulation of the conductive high-molecular dispersion liquid and the electrolyte and the corresponding process parameters are adjusted, as follows:

[0086] S4, conductive high-molecular dispersion liquid immersion: under the alternating cycle of vacuum and pressure, the core package after drying treatment is immersed in the prepared conductive high-molecular dispersion liquid.

[0087] The conductive high-molecular dispersion liquid is composed of the following components in mass percentage: 82.1% of pure water, 16.8% of polymer monomer, 0.35% of doping acid, 0.55% of nano copper oxide, and 0.2% of sodium salt.

[0088] Specifically, in this embodiment, the polymer monomer is aniline, the doping acid is salicylic acid, and the sodium salt is sodium nitrate.

[0089] S6, electrolyte immersion: under vacuum, the core package after polymerization treatment is immersed in the prepared electrolyte.

[0090] The electrolyte is composed of the following components in mass percentage: 48% of sulfolane, 32.7% of gamma-butyrolactone, 10% of ethylene glycol, 9% of triethylamine phthalate, and 0.3% of additives.

[0091] The additive contains the following components in mass fraction, based on the total mass of the electrolyte: 0.15% of chloride, 0.05% of sulfate, 0.06% of inorganic high-molecular iron salt, and 0.04% of heavy metal compound.

[0092] Specifically, in the embodiment, the chloride is sodium chloride, the sulfate is ammonium sulfate, the inorganic high-molecular iron salt is polyaluminum chloride, and the heavy metal compound is cadmium sulfate.

[0093] The remaining steps of the embodiment, such as S1 element winding, S2 formation repair, S3 drying treatment, S5, thermal polymerization, S7 packaging, and S8 aging, are the same as those of Embodiment 1.

[0094] Table 4: Test results of high-temperature durability test of the capacitor sample of Embodiment 4

[0095]

[0096] According to the performance test data of Embodiments 1 to 4, the solid-liquid mixed capacitor prepared by using the technical scheme of the application has an average capacitance attenuation rate of -1.08% to -1.44% after undergoing a severe high-temperature durability test at 150°C for 2000 hours, which is an extremely narrow range, and exhibits excellent high-temperature stability.

[0097] This breakthrough performance is due to the synergistic innovation of material system and structural design: nano-copper oxide significantly enhances the electrochemical activity and material performance of conductive polymers by improving reaction efficiency and product performance, and sodium ions improve the thermal stability of the target polymer by changing the electronic structure and energy group distribution, thereby forming a stable conductive network skeleton at high temperatures; in this process, the doping acid (such as p-toluenesulfonic acid) acts as a dopant and catalyst, which not only improves the conductivity by providing doping anions, but also promotes polymerization by adjusting the pH, and forms a synergistic system with nano-copper oxide and sodium salt to optimize material synthesis and performance; finally, the solid layer plays a role in thermal stability support, and the electrolyte formula supplements the deficiency of the solid layer, effectively reduces the internal heating of the product by improving the voltage resistance and improving the leakage current, and this synergistic mechanism of "solid support and liquid repair" significantly improves the overall heating capacity of the product, and realizes long-term stable operation in a 150°C environment.

[0098] Comparative Example 1

[0099] The present comparative example provides a preparation method of a capacitor, which is different from Embodiment 1 in that, in the S4 step, the conductive polymer dispersion liquid is composed of the following components in mass percentage: 83% of pure water and 17% of polymer monomer, and does not contain doping acid, nano-copper oxide, and sodium salt in the dispersion liquid.

[0100] The S6 electrolyte impregnation step is omitted.

[0101] The remaining steps of the present comparative example, such as S1 element winding, S2 formation repair, S3 drying treatment, S5 thermal polymerization, S7 packaging, and S8 aging, are the same as those of Example 1.

[0102] Table 5, test results of the high-temperature durability test of the capacitor sample of Comparative Example 1

[0103]

[0104]

[0105] As can be seen from the data in Table 5, the performance of the present comparative example is severely degraded, with an average capacitance attenuation rate of -24.51% after 2000 hours of aging at 150°C, which is much higher than that of the present application, and the ESR increases sharply, indicating that the product has completely failed. The root cause is that the dispersion liquid only contains pure water and polymer monomers, lacks doped acid, resulting in extremely low conductivity of the conductive polymer; lacks nano copper oxide, resulting in loose structure of the solid electrolyte layer generated by polymerization reaction; lacks sodium salt to stabilize the electronic structure of the polymer chain. At the same time, there is no repair effect of the electrolyte, which ultimately leads to the sharp deterioration of the capacitor characteristics, and this result proves that the traditional pure solid-state scheme cannot meet the application requirements of 150°C extreme high temperature.

[0106] Comparative Example 2

[0107] The present comparative example provides a method for preparing a capacitor, which is different from Comparative Example 1 in that:

[0108] In the S4 step, the conductive polymer dispersion liquid is composed of the following components by mass percentage: pure water 82.7%, polymer monomer 17%, and doped acid 0.3%, and the dispersion liquid does not contain nano copper oxide and sodium salt.

[0109] The remaining steps of the present comparative example are the same as those of Comparative Example 1.

[0110] Table 6, test results of the high-temperature durability test of the capacitor sample of Comparative Example 2

[0111]

[0112]

[0113] From the data in Table 6, the performance of the comparative example is improved compared to comparative example 1, but is still severely unqualified, with an average capacitance decay rate of -8.37%. The improvement is due to the introduction of the doping acid, which provides the necessary doping of the conductive polymer. However, due to the lack of nano-copper oxide to improve the efficiency and density of the polymerization reaction, and the lack of sodium salt to further improve the thermal stability, the solid electrolyte layer itself has structural defects, and without the protection of the electrolyte, the product will still fail quickly at high temperatures. This result proves that simply adding a doping acid is far from enough.

[0114] Comparative example 3

[0115] The comparative example provides a method for preparing a capacitor, which is different from comparative example 1 in that:

[0116] In the S4 step, the conductive polymer dispersion liquid is composed of the following mass percentages of components: pure water 82.4%, polymer monomer 17%, doping acid 0.3%, and nano-copper oxide 0.6%, and does not contain sodium salt in the dispersion liquid.

[0117] The remaining steps of the comparative example are the same as those of comparative example 1.

[0118] Table 7, electrical performance test results of comparative example 3 capacitor sample high temperature durability test

[0119]

[0120]

[0121] From the data in Table 7, the performance of comparative example 3 is further improved compared to comparative example 2, but still does not meet the requirements, with an average capacitance decay rate of -3.40%. The improvement is due to the addition of nano-copper oxide, which significantly improves the density and electrochemical activity of the solid layer. However, the lack of sodium salt to stabilize the energy level structure of the conductive polymer can still cause irreversible degradation of the polymer chain at high temperatures over a long period of time, and the lack of electrolyte prevents the weak points of the anode foil from being repaired. This result proves the indispensable role of sodium salt in improving long-term high-temperature stability.

[0122] Comparative example 4

[0123] The comparative example provides a method for preparing a capacitor, which is different from comparative example 1 in that:

[0124] An S6 electrolyte impregnation step is added, and the composition and process of the electrolyte are the same as those of example 1.

[0125] The remaining steps of the comparative example are the same as those of comparative example 1.

[0126] Table 8, electrical performance test results of comparative example 4 capacitor sample high temperature durability test

[0127]

[0128]

[0129] From the data in Table 8, the performance of the comparative example is still poor, with an average capacitance decay rate of -10.27%. This shows that under the premise of using the same poor dispersion liquid as Comparative Example 1, even if the same electrolyte impregnation step as Example 1 is added, the overall performance cannot be saved. The root cause of failure is that the poor solid electrolyte layer rapidly degrades itself at high temperature, at which point the repair effect of the electrolyte cannot offset the impact caused by the failure of the solid layer. This result strongly proves that "optimizing the solid electrolyte layer" is the core and foundation of the present application.

[0130] Comparative Example 5

[0131] The present comparative example provides a method for preparing a capacitor, which differs from Comparative Example 2 in that:

[0132] An S6 electrolyte impregnation step is added, and the electrolyte composition and process are the same as in Example 1.

[0133] The remaining steps of the present comparative example are the same as those of Comparative Example 2.

[0134] Table 9, Test results of high-temperature durability test of electrical properties of capacitor samples of Comparative Example 5

[0135]

[0136]

[0137] From the data in Table 9, the performance of the present comparative example is improved compared to Comparative Examples 2 and 4, with an average capacitance decay rate of -5.78%, but it is still far from the present application. The reason for the improvement is that the electrolyte plays a key role in repairing the anode oxidation film defects. However, due to the instability of the solid electrolyte layer itself due to the lack of nano-copper oxide and sodium salt, it will still gradually degrade at high temperature for a long time, leading to continuous decay of the capacitance. This result ultimately proves that only by combining the optimized solid electrolyte layer with the optimized electrolyte can the best synergistic effect be achieved.

[0138] Obviously, the above-described embodiments are only some embodiments but not all the embodiments of the present application, and are not intended to limit the patent scope of the present application. The present application can be implemented in many different forms, and contrary to the above-described embodiments, the purpose of providing these embodiments is to make the disclosure of the present application more thorough and comprehensive. Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still make modifications to the technical solutions recorded in the foregoing specific embodiments, or make equivalent replacements to some technical features therein. Any equivalent structure made by using the content of the present application, directly or indirectly applied to other related technical fields, is also within the patent protection scope of the present application.

Claims

1. A method for preparing a high-temperature resistant solid-liquid hybrid capacitor, characterized in that, Includes the following steps: S1. Core winding: Electrolytic paper is inserted between the anode foil and the cathode foil and wound into a core package; S2, Formation Repair: The core package is immersed in the formation solution to repair the anodic oxide film; S3. Drying treatment: The core package that has undergone chemical repair is baked to remove moisture; S4. Impregnation with conductive polymer dispersion: Immerse the dried core package in a conductive polymer dispersion. S5. Thermal polymerization: The impregnated core package is baked to polymerize the monomers and form a conductive polymer solid electrolyte layer. S6. Electrolyte impregnation: Immerse the polymerized core package in the electrolyte; S7. Packaging: Pack the electrolyte-impregnated core into the outer casing and seal it; S8. Aging: Aging treatment is performed on the packaged capacitors; The conductive polymer dispersion contains polymer monomers, doped acid, nano-copper oxide, and sodium salt.

2. The preparation method according to claim 1, characterized in that, The conductive polymer dispersion comprises, by total mass, 14%–19% polymer monomer, 0.25%–0.35% doped acid, 0.55%–0.65% nano copper oxide, 0.1%–0.2% sodium salt, and the balance being pure water.

3. The preparation method according to claim 1, characterized in that, The electrolyte contains a solvent and additives, the additives including chlorides, sulfates, inorganic polymeric iron salts, and heavy metal compounds.

4. The preparation method according to claim 2, characterized in that, The polymer monomer is at least one of aniline, pyrrole, thiophene and their derivatives; the doped acid is selected from at least one of organic sulfonic acid or organic carboxylic acid; the sodium salt is selected from at least one of sodium chloride, sodium sulfate, sodium nitrate, sodium acetate and sodium citrate.

5. The preparation method according to claim 2, characterized in that, The particle size of the nano-copper oxide is 25nm to 45nm.

6. The preparation method according to claim 3, characterized in that, The electrolyte comprises, by total mass, 42%–67% sulfolane, 24.6%–48% γ-butyrolactone, 5%–10% ethylene glycol, 2.8%–9% triethylamine phthalate, and 0.3%–1% additives.

7. The preparation method according to claim 6, characterized in that, Based on the total mass of the electrolyte, the additives comprise: 0.15% to 0.5% chloride, 0.05% to 0.3% sulfate, 0.06% to 0.12% inorganic polymeric iron salt, and 0.04% to 0.08% heavy metal compounds.

8. The preparation method according to claim 7, characterized in that, The chloride is selected from at least one of ammonium chloride, sodium chloride, potassium chloride, and choline chloride; the sulfate is selected from at least one of ammonium sulfate, sodium sulfate, and magnesium sulfate; the inorganic polymeric iron salt is selected from at least one of polyferric sulfate and polyferric chloride; and the heavy metal compound is selected from at least one of lead-containing compounds, mercury-containing compounds, cadmium-containing compounds, or chromium-containing compounds.

9. The preparation method according to claim 1, characterized in that, In step S1, the electrolytic paper is a low-density mixed fiber electrolytic paper; in step S5, the baking temperature is 140℃~160℃ and the time is 25~35 minutes; steps S4 and S5 need to be repeated 3 to 5 times; the impregnation in step S4 is carried out in a cyclic environment of alternating vacuum and pressure; the impregnation in step S6 is carried out in a vacuum environment.

10. A high-temperature resistant solid-liquid hybrid capacitor, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Solid-liquid hybrid capacitor and manufacturing method thereof

    CN112435863A